Residents' attitudes to tourism development: The case of Cyprus - Akis, S; Peristianis, N; Warner, J (Elsevier Sci Ltd, 1996)
This paper examines the perceptions of Creek and Turkish Cypriot residents of coastal tourism development. Although Butler's hypothesis - that there will be an inverse relationship between the level of tourism development and perceived impacts for the worse on the social, economic and environmental status of the host community - is largely confirmed, a significant proportion of uncertain responses in the less developed area surveyed lead us to suggest a modification of the Butler hypothesis. Copyright (C) 1996 Published by Elsevier Science Ltd
Keywords: tourism development; Cyprus; Greek; Turkish; residents' attitudes